Simultaneous immobilization of lead, cadmium and arsenic in soil by iron-manganese modified biochar - Yang, Zhihui; Zeng, Gai; Liu, Lin; He, Fangshu; Arinzechi, Chukwuma; Liao, Qi; Yang, Weichun; Si, Mengying (Frontiers in Environmental Science, 2023)
Cationic lead/cadmium and anionic arsenic exhibit opposite geochemical behaviors in soils, which makes the synchronous remediation of As, Cd, and Pb challenging. In this study, we developed an iron-manganese modified biochar (BC-Fe-Mn) that prepared from straw with iron (Fe) and manganese (Mn) loading at a pyrolysis temperature of 550 °C. After BC-Fe-Mn immobilization for 90 days, the simultaneous immobilization efficiency of Pb, Cd, and As reached 57%, 51%, and 35%, respectively. Speciation distributions shows that As transformed from specific bound state into weakly low crystallinity iron bound state. Cd transformed from carbonate fraction into Fe-Mn oxide bound fraction, and Pb transformed from carbonate fraction into residual state. During the procedure, simultaneous immobilization mechanisms might involve heavy metal morphological transformation, precipitation/co-precipitation, and surface complexation. Cd and Pb absorbed onto BC-Fe-Mn. Then the increased free iron oxides (Fed) reacted with the dissolved As to form iron-arsenic precipitation. The results show that BC-Fe-Mn is a promising material for the simultaneous immobilization of Pb, Cd, and As in multi-metal contaminated soil.